2022
DOI: 10.1038/s41598-022-20789-1
|View full text |Cite
|
Sign up to set email alerts
|

A tuff interlayer in deep potash-bearing salt rocks and its implication for potash mineralization in the Simao Basin, southwestern China

Abstract: The lithology and genesis of a dark grey clastic interlayer first encountered within the deepest potassium-rich salt body in the Simao Basin, southwestern China, were analysed. Analyses of the petrography, mineralogy, and element geochemistry of the layer revealed that (1) the layer contains quartz crystals with gulf corrosion edges and explosion cracks and angular volcanic ash-sized glasses; (2) the main mineral components of the crystal fragments are chlorite, illite, biotite, quartz, anhydrite, gypsum, magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The δ 34 S V-CDT values of anhydrite with similar depth (2524.4 to 2526.1 m) range from 15.1‰ to 15.5‰. The δ 34 S V-CDT value of anhydrite deposited in the early stage (at a depth of 2627.8 m) is 15.5‰ [3]. It is concluded that pyrite is of sedimentary origin and H 2 S generated by anhydrite formed in the early biodegradation stage is an important sulfur source.…”
Section: The Origin Of Pyritementioning
confidence: 95%
See 4 more Smart Citations
“…The δ 34 S V-CDT values of anhydrite with similar depth (2524.4 to 2526.1 m) range from 15.1‰ to 15.5‰. The δ 34 S V-CDT value of anhydrite deposited in the early stage (at a depth of 2627.8 m) is 15.5‰ [3]. It is concluded that pyrite is of sedimentary origin and H 2 S generated by anhydrite formed in the early biodegradation stage is an important sulfur source.…”
Section: The Origin Of Pyritementioning
confidence: 95%
“…The Simao Basin can be divided into four uplifts and four depressions, a total of eight second-order tectonic units (see Figure 1), and the sedimentary strata are mainly Mesozoic-Cenozoic [13,14]. Salt rocks discovered in the basin are mainly found in the Mengyejing Formation of the Lower Cretaceous, with a maximum burial depth above 1251 m. From west to east, salt rocks can be divided into the Jinggu salt-bearing belt, Zhengdong-Mengla salt-bearing belt, and Jiangcheng salt-bearing belt [2,15]. The surrounding rock of salt rock is mainly mud-clast conglomerates, and there is no carbonate rock and sulfate rock of corresponding scale in normal evaporative deposition sequence, and mud-clast conglomerates often appear in salt rock [16,17].…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations